The development of a Thai word discrimination by picture identification test - Chermak, Gail D; Phanijphand, Nualnipha B (Journal of All India Institute of Speech and Hearing)
A Thai word discrimination by picture identification test was developed. Phonemic and tonemic contrasts comprised the fine and gross discriminations. Four lists of 25 words each were randomly assembled. Twelve normal hearing native adult Thai speakers served as subjects. The test was administered to each subject both auditorally and auditorally with the closed-set visual cues provided by the pictures. Pearson’s product moment correlation coefficients revealed significant correlations between 2 and 3 pairs of lists only when presented in the combined auditory (closed-set)-visual mode and the auditory mode, respectively. Modifications need to be incorporated before this test is clinically reliable. Limitations of the present study in terms of subjects was discussed